AN AUTISTIC CHARACTER’S CONFLICT IN MARK HADDON’S THE CURIOUS INCIDENT OF THE DOG IN THE NIGHT-TIME - Cici Andriani Pardede; Selly Roida Samosir; Desmalia Purba (LPPM Universitas Darma Agung, 2021)
This thesis deals with a conflict of an autistic character in Mark Haddon’s The Curious Incident of the Dog in the Night-Time. The problems of the study are, the kinds of conflict, the causes of the conflict, and the impact of conflict on Christopher, as the main character in Mark Haddon’s novel. This thesis applies the qualitative research method. Christoper’s internal conflict is suffering from Asperger Syndrome as an autism spectrum disorder which in turn affects his overall behavior because the autism he suffers limits his actions and thoughts. He uses his normative way of making sense of his surrounding and seeks the mysterious death of the dog whereas Christopher’s external conflict such as man against. man and man against the society. This story emphasizes the different perspective that tells about what the main character gets through compared to people in general. He gets through various trials, gains confidence in his abilities and slowly changes to be more self-sufficient.